Prevalence and factors associated with anaemia among pregnant Women in their second and third trimester attending Antenatal care at Kisoro district hospital, Kisoro District: A Cross-sectional Study. - Oburu, Ivan; Atai, Sarah; Kesande, Annet; Isingoma, Jenu; Atukwase, Christian; Kisirikko, Christine; Mukiibi, Yasin (Student's Journal of Health Research Africa, 2022)
Background: There is an increase in the incidence of anemia among pregnant women in Uganda despite the several interventions implemented during antenatal care clinics in public and private health care facilities. Purpose: To determine the prevalence of anemia and its associated factors among pregnant women seeking antenatal care in Kisoro District Hospital in Kisoro district. Methods: A cross-sectional study was conducted among 265 pregnant women who were selected by simple random technique from the ANC clinic. Blood samples were collected and their Haemoglobin levels were estimated for anaemia. A questionnaire was administered to the pregnant women who consented to the study to establish the factors associated with anaemia. Data were analyzed in univariate and bivariate using the chi-square test to determine factors associated with anaemia at a 95% confidence interval. Results: Findings showed that the prevalence of anaemia among pregnant women in their second and third trimesters was 14% (37/265). The prevalence of anaemia was high among pregnant women in the second trimester compared to the third trimester. A total of 158 (59.6%) pregnant women were in the second trimester out of which 24 (15.2%) pregnant women were anaemic. There were 107 (40.4%) pregnant women in the third trimester of pregnancy and 13 (12.1%) were diagnosed with anaemia. The factors associated with anaemia included recent malaria infection (p=0.001), not eating a balanced diet (p=0.032), and irregular taking of iron and folate tablets (fefo) (p<0.05). Conclusion and recommendation: Anaemia is lower than the national average which reveals its existence in this population. Pregnant women should be monitored regularly for proper control and preventive measures of malaria in pregnancy. Stakeholders should promote dietary diversity and the improvement of socioeconomic status at the household level. Need to improve the frequency of antenatal visits, as means to monitor the intake of fefo tablets.